The impact of dental anxiety on the salivary cortisol and alpha-amylase levels of children undergoing dental treatment - Majed AlMaummar; Huda Othman Althabit; Sharat Chandra Pani (Wolters Kluwer Medknow Publications, 2019)
Background and Aim: The purpose of this study was to assess the salivary cortisol and salivary alpha-amylase levels in children aged between 6 and 9 years immediately prior to dental treatment. Methodology: A total of 183 patients aged between 6 and 9 years who were awaiting dental treatment were administered the Arabic version of the Children's fear survey - dental subscale and accordingly allocated to one of three groups: phobic patients, anxious patients, and control group. Patients' heart rate in the waiting area, salivary cortisol, and salivary amylase were compared among the groups. Results: The results of the study showed that amylase and cortisol levels had a significant association with the level of dental fear. The phobic patients had the highest levels of salivary amylase and salivary cortisol levels with no significant associations observed with either heart rate. Control and anxious patients had significantly lower amylase levels when compared to phobic patients. There was no significant difference between the salivary cortisol levels of anxious and phobic patients. Conclusions: Within the limitations of this study, we can conclude that salivary amylase is a good indicator of acute stress that can differentiate between anxiety and dental fear, while salivary cortisol is a good indicator of the phobia induced by a flight or fight response.